Supplementary testing after negative or inconclusive exome sequencing results - Balsam AlMaarik; Taghrid Aloraini; Roselyn Paclejan; Mohammed Balwi; Lamia Alsubaie; Abdulrahman Alswaid; Wafaa Eyiad; Fuad Al Mutairi; Faroug Ababneh; Majid Alfadhel; Ahmed A. Alfares (Journal of Biochemical and Clinical Genetics, 2023)
Background: Accurate diagnosis benefits patients and their families by directing clinical management; predicting recurrence risks; providing prognosis; and preventing the invasive, time-consuming, and costly diagnostic odyssey. The present study aimed at evaluating the usefulness and clinical utility of supplementary testing (deletion/duplication, targeted genome methylation analysis, and whole mitochondrial genome testing) after inconclusive or negative exome results and the outcome of the supplementary testing. Methods: A total of 3,505 clinical exome sequencing results were evaluated, and cases with supplementary testing were analyzed for the accuracy and validity of the supplementary testing. Results: The present study cohort comprised 26 cases where supplementary testing was ordered (12 inconclusive results and 14 negative results). Out of the 12 inconclusive results, only one case was positive for supplementary testing (1/12) and none of the negative cases (0/14). Conclusion: For most cases, supplementary testing to negative exome sequencing failed to identify any possible explanation of the disorder, concluding that supplementary testing has limited clinical utility. [JBCGenetics 2023; 6(1.000): 1-13]